Is the Arctic really urbanising? - Dybbroe, Susanne (Études/Inuit/Studies, 2008)
AbstractThe anthropology of the Arctic (Inuit) societies is increasingly acknowledging a general urbanising trend throughout the region, encompassing small-scale, localized, communities as well as towns and cities. Inuit migrate to cities outside the Arctic and live in the North under circumstances strongly tinged by urbanism. Policy and academic literature suggests that there is an increasingly close relation between Arctic residents and cities. After an historic overview of permanent settlement in Nunavut and Greenland to illustrate the structural integration of Arctic societies, this article points to the fact that urbanisation follows historically specific trajectories and creates different urban situations. The author discusses the relevance of the concepts “urbanisation” and “urbanism” to the Arctic, and proposes an urban anthropological perspective that offers a productive way to approach the globalised social and cultural realities of the contemporary Arctic.